Strengthening of water-saturated soils of the bases of underground structures with composite solutions modified by industrial waste, boehmite. (June 2020) - Panfilova, Marina I.; Zubrev, Nikolai I.; Efremova, Saniya Y.; Yakhkind, Michael I.; Gorbachevskii, Valentin P.
Abstract: Technological measures have been developed for establishment of the underground part of a capital construction object on weak and water-saturated soils in order to ensure the integrity and safety of the underground structures that include into the zone of influence of new construction. The possibility of the use of the composite solutions with the addition of waste, boehmite, formed in hydrogen production from aluminum to establish "wall in soil" and to prevent its horizontal shift, as well as to strengthen the bases of existing buildings standing on water-saturated soils has been proved. A method for transformation of a composite system by modification with boehmite, the integration of which promotes an increase in density and strength of the mortar mixture has been proposed.